2022
DOI: 10.1021/acsanm.2c01774
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Cure Vapor-Grown Carbon Nanofiber-Supplemented 3D-Printed Resin: Implications for Improved Stiffness and Thermal Resistance

Abstract: Stereolithography (SL), often referred to as an advanced manufacturing technique, is employed to conveniently fabricate bulk and delicate objects with UV-curable resin due to its high accuracy and versatility. However, the poor performance exhibited by UV-curable resin limits the practical applicability of SL. In this study, the acidified vapor-grown carbon nanofibers (VGCFs)-supplemented dual-cure 3D-printed SL resin nanocomposites are prepared by a facile method to avoid nonhomogeneous curing and improve the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…To meet specific application requirements, researchers primarily enhance the thermal resistance, 134 mechanical properties, 135 antioxidation, 136 or wear resistance 137 of photosensitive resins by incorporating other polymers or nanofillers (such as carbon nanofibers, 138 graphene nanosheets, 139 nano SiO 2 , 140 nano TiO 2 , 141 nano copper particles, 142 etc.). Chen et al 143 developed a kind of 3D printing photosensitive resin with excellent thermal resistance and mechanical properties by adding a novel bismaleimide resin (BDM‐DDM‐GMA) and acrylate liquid crystal resin (ALCR) to a commercial photosensitive resin mixture (BDM/ALCR‐0, mainly including aliphatic polyurethane acrylates, polyurethane acrylates, polyethylene glycol and TPO photoinitiator) (Figure 8A).…”
Section: Development Of 3d Printable Polymer Composite Consumablesmentioning
confidence: 99%
“…To meet specific application requirements, researchers primarily enhance the thermal resistance, 134 mechanical properties, 135 antioxidation, 136 or wear resistance 137 of photosensitive resins by incorporating other polymers or nanofillers (such as carbon nanofibers, 138 graphene nanosheets, 139 nano SiO 2 , 140 nano TiO 2 , 141 nano copper particles, 142 etc.). Chen et al 143 developed a kind of 3D printing photosensitive resin with excellent thermal resistance and mechanical properties by adding a novel bismaleimide resin (BDM‐DDM‐GMA) and acrylate liquid crystal resin (ALCR) to a commercial photosensitive resin mixture (BDM/ALCR‐0, mainly including aliphatic polyurethane acrylates, polyurethane acrylates, polyethylene glycol and TPO photoinitiator) (Figure 8A).…”
Section: Development Of 3d Printable Polymer Composite Consumablesmentioning
confidence: 99%
“…11 Nanoparticles and other nanomaterials represent a specific category of fillers with pronounced interfacial effects. 12 They are favored for nanoreinforcement, 13 functional additivation, 14,15 and, generally, a simple modification of properties. 16 Davtyan, et al reported an almost negligible effect of silica nanoparticles (NPs) on the front propagation and temperature of PMMA/methyl methacrylate solution up to the concentration corresponding to the NP aggregation limit.…”
Section: Materials Horizonsmentioning
confidence: 99%
“…The evolution of 3D printing technology has made significant strides since Charles Hull introduced early stereolithography (SLA) systems for manufacturing in the 1980s . Currently, SLA and DLP are the two most commonly used 3D printing technologies, representing approximately 43% of the market. , UV-curing 3D printing technology utilizes ultraviolet lasers to scan photosensitive resins layer by layer, enabling the gradual construction of objects. , This technology allows for the independent design and production of intricate parts with high precision and high material efficiency. The photosensitive resin reacts with UV light, triggering a rapid curing process.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 UV-curing 3D printing technology utilizes ultraviolet lasers to scan photosensitive resins layer by layer, enabling the gradual construction of objects. 4,5 This technology allows for the independent design and production of intricate parts with high precision and high material efficiency. The photosensitive resin reacts with UV light, triggering a rapid curing process.…”
Section: Introductionmentioning
confidence: 99%